The Hazard Analysis Critical Control Point (HACCP) in Food Service in Sariharjo, Ngaglik, Sleman Regency - Amini, Noor Rosyidah; Shinta APRILIA (RADINKA JAYA UTAMA PUBLISHER, 2024)
This research aims to find out the HACCP in catering A, B, and C and the quality as seen from microbiological, physical, and chemical contamination. This descriptive research uses a purposive sampling method to take the sample of catering, and random sampling to take samples of fried chicken. The result data of observation and questionnaire sheets are analyzed by the researcher based on HACCP application and National Standardization Corporation (BSN), then analyzed by tests of microbiological contamination including the extrapolation of Total Plate Count (TPC), MPN Coliform, and the existence of Escherichia coli, test of physical contamination including taste, scent, color, appearance, texture, and the existence of unknown things, and also tests of chemical contamination including quantitative test of Monosodium Glutamate (MSG), qualitative test of formalin, and pH measurement. The time of research started from March until May 2015. The sample used is fried chicken from catering A, B, and C. The results are catering A and B have percentages of 67.34% and 66,69% with a critical point on the packing step, and catering B has a percentage of 57.74% with a critical point on the processing and packing step. The result of TPC on the fried chicken sample of catering A and B is more than standard, MPN Coliform of the three samples is more than standard, and E.coli is found on the fried chicken sample of catering B. The BMP of MSG examined on three samples of catering A, B, and C are 13.200 mg/kg and there is no formal found on the three samples. The rancidity is only found in the sample of catering A, and besides pink color is only found in the sample of catering C.